Engineering And Microstructural Characterization Of Marine Clay Treated With Cement And Lime - Meow, Lian Ke (Universiti Sains Malaysia, 2022)
Soil is significant in the construction of roads and the foundation of building structures. Problematic soil such as marine clay soil would cause significant disruption and poor performance of civil infrastructure. In this study, marine clay soil is selected as soil samples in soil stabilization. The aim of this research is to determine the engineering and microstructural characteristics of marine clay treated with cement and lime. The natural moisture content is determined and followed by specific gravity test, Atterberg limit test and particle size analysis. For standard proctor test, 3 %, 5 %, 7 %, 9 % and 11 % of lime and 10 %, 15 % and 20 % of cement are mixed to the marine clay soil for chemical stabilization. Unconfined compression strength test and X-ray Fluorescence analysis are carried out to compare the UCS value and microstructural changes of non-stabilized marine clay with optimum percentage of 11 % lime additives and 20 % cement additives after curing for 7 days. The increment of percentage of both lime and cement result in the increase of maximum dry density and decrease of optimum moisture content. The UCS test of marine clay with admixture such as lime and cement have larger value compared to non-stabilized marine clay through pozzolanic reaction. In microstructural characteristics, non-stabilized marine clay were dominants by three element oxides including aluminium oxide (Al2O3), silica oxide (SiO2) and ferric oxide (Fe2O3). However, marine clay stabilized with 11 % of lime and 20 % of cement were dominants by three dominants element oxides above and calcium oxide (CaO). This research and findings will contribute extra knowledge on understanding the mechanism of these stabilizing agents.